PERLINDUNGAN HUKUM TERHADAP ANAK BERISIKO MENGALAMI SECONDARY PRISONIZATION AKIBAT ORANG TUA SEBAGAI PELAKU TINDAK PIDANA TERORISME - Khairunnisa Khairunnisa; Davit Rahmadan; Ledy Diana (Jurnal Ilmiah Wahana Pendidikan, 2023)
Legal protection for children is defined as an effort to protect the law against the freedom and human rights of children related to their welfare. Children as human beings are treated equally regardless of gender, age, race, and ethnicity. However, in practice, children of perpetrators of criminal acts of terrorism often experience discrimination, stigmatization and persecution in their lives. Stigmatization and labeling that are not handled properly will lead to resentment and adjustments in a child's behavior according to what is labeled, namely being a terrorist. This research uses normative legal research or also known as doctrinal legal research which uses secondary data sources using primary legal materials, secondary legal materials, and tertiary legal materials. In this normative research, researchers conducted research on vertical and horizontal legal synchronization. This study discusses legal protection arrangements for children at risk of experiencing secondary prisonization, the impact of secondary prisonization on children and efforts to overcome stigmatization of children at risk of experiencing secondary prisonization